Antifungal Potential of Cladosporium sp. (Endophytic fungi) Associated with Olea europaea L. Leaves (Baghdad Science Journal, 2023)
In the leaves of Olea europaea L. Olive trees an endophytic fungus was discovered. Cladosporium sp. was identified to be the fungus based on its morphological characteristics and nuclear ribosomal DNA ITS sequence analysis and was registered in NCBI as the Cladosporium genus has been registered under the number (0P939922.1) The species was not specified, and it was considered of unknown species after comparing it to global isolates. In comparison to olive leaf extract, Cladosporium sp. including total flavonoid, total phenolic, total terpenoid, and total saponins, Which were 121.9%, 198.1%, 89.13%, and 29.87 % respectively compared to its content in olive leaf extract, which was 61.54 %, 67.88 % , 17.1%, and 20.19% respectively. The Cladosporium sp. extract inhibited the growth of 27 isolates belonging to different species of candida which were Candida albicans , C. lypolitica , C. tropicalis , C. sphaerica , C. krusei , C. guilliermondii , C. parapsilosis , C. norvegicus , C. glabrata , and C. kefyr , the inhibition effects increased with increasing concentration to reach the highest level to suppress fungal growth when concentrated 30 mg/ml. This proves the antifungal potential of endophytic fungi in the future.